2012
DOI: 10.3928/01477447-20120525-25
|View full text |Cite
|
Sign up to set email alerts
|

External Fixation Versus ORIF for Distal Intra-articular Tibia Fractures

Abstract: Tibia plafond fractures have historically demonstrated high complication rates. The purpose of this study was to assess the outcomes of tibia plafond fractures following treatment with definitive external fixation vs delayed open reduction and internal fixation (ORIF). Sixty patients were enrolled in a prospective cohort trial at 1 Level I trauma center. No differences were noted between the 2 treatment groups in terms of age, smoking history, presence of comorbidities, mechanism of injury, incidence of open f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
(45 reference statements)
2
35
0
Order By: Relevance
“…15 A total of 3 studies involving 141 fractures reported the results of delayed union. The rate of delayed union was 5 of 78 fractures in the two-stage ORIF group and 9 of 63 fractures in the LIFEF group.…”
Section: Resultsmentioning
confidence: 99%
“…15 A total of 3 studies involving 141 fractures reported the results of delayed union. The rate of delayed union was 5 of 78 fractures in the two-stage ORIF group and 9 of 63 fractures in the LIFEF group.…”
Section: Resultsmentioning
confidence: 99%
“…[31,32] The assessment of the included cohort studies suggests that two studies [20,30] had unbalanced prognostic factors of the patients in their cohorts as they did not match patients in the design nor did they adjust for important compounding factors, in contrast to the rest of the cohort studies. In addition, the studies of Anglen [20] Davidovitch et al, [27] Guo et al, [29] and Richards et al [28] did not have an adequate follow-up with >20% of their patients lost to follow-up. The included RCTs [19,26] carried a high risk of bias, especially in blinding and concealment of patients and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles directly comparing LIFEF and ORIF for the treatment of pilon fracture were included in this meta-analysis, including one randomized controlled trial (RCT), 19 one cohort study 12 and 7 retrospective studies 15, 20, 21, 22, 23, 24, 25. Totally 498 fractures in 494 patients were included in this study, and all eligible patients were followed up for at least 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…Because ORIF can restore the anatomic structure of distal tibia, it has been regarded as a safe surgical procedure with good results. However, the extensive dissection of soft tissue might lead to increased complications, such as infection, skin necrosis, tensity wheal and other complications 11, 12, 13, 14. LIFEF has been widely used for pilon fracture in recent years, but results in poor restoration of articular surface and high rates of traumatic arthritis 15, 16, 17.…”
mentioning
confidence: 99%